THE LEIOGNATHIDAE (TELEOSTS): AN HYPOTHESIS RELATING THEIR MEAN DEPTH OCCURRENCE TO THE INTENSITY OF THEIR COUNTERSHADING BIOLUMINESCENCE - Pauly, Daniel (Marine Research in Indonesia, 1977)
All species belonging to the Family Leiognathidae (genera Leiognathus, Secutor & Gazza) are bioluminescent. They emit during daytime a downward, diffuse light which tends to disrupt their silhouette, making them less discernible from beneath to potential predators. It is here assumed that the intensity of light emitted should correspond to the intensity of incident light at the depth at which each species generally occurs. Using published information on the relative intensity of emitted light in different species and quantitative data on the mean depth occurrence of the species, it is shown that there is a good correspondance in the ranking order of both light intensity and depth occurrence in five species (e.g. Secutor ruconius emits a strong light and occurs in shallow water; Leiognathus elongatus emits a weak light and occurs at greater depth). Species not fitting into this pattern (e.g. Leiognathus splendens emits a weak light but occurs in very shallow water) tend to occur in murky water, where less light is required for counterillumination.